A British Cardiac Society survey of the potential for the secondary prevention of coronary disease: ASPIRE (Action on Secondary Prevention through Intervention to Reduce Events). Issue 4 (April 1996) - Bowker, T. J.; Clayton, T. C.; Ingham, J.; McLennan, N. R.; Hobson, H. L.; Pyke, S. D.; Schofield, B.; Wood, D. A.
Abstract : OBJECTIVE: To measure the potential for secondary prevention of coronary disease in the United Kingdom. DESIGN: Cross sectional survey of a representative sample of coronary patients from a retrospective review of hospital medical records and patient interview and examination. SETTING: Stratified random sample of 12 specialist cardiac centres and 12 district general hospitals drawn from 34 specialist cardiac centres and 261 district general hospitals in 12 geographic areas in the United Kingdom. SUBJECTS: 2583 patients < or = 70 yr; 25 consecutive males and 25 consecutive females identified retrospectively in each of four diagnostic categories: coronary artery bypass grafting, percutaneous transluminal coronary angioplasty, acute myocardial infarction, and acute myocardial ischaemia without evidence of infarction. MAIN OUTCOME MEASURES: Risk factor recording and management in medical records; the prevalence and control of risk factors at interview six months after the procedure or event. RESULTS: Recording of coronary risk factors in patient's records was incomplete and this varied by risk factor. Smoking habit and blood pressure were most completely recorded, whereas a history of hyperlipidaemia and blood cholesterol concentrations were least complete. Risk factor records were more likely to be complete in cardiac centres than in district hospitals. At interview 10% to 27% of patients were still smoking cigarettes and 75% remained overweight, females more severely so. Up to a quarter of patients remained hypertensive, males more severely so than females. Over three quarters had a total cholesterol > 5.2 mmol/l. In patients on medication for blood pressure, cholesterol or glucose, risk factor profiles were little better than in those who were not. Only about one patient in three was taking a beta blocker after infarction. Up to a fifth of patients who had had acute myocardial ischaemia were not taking aspirin at follow up. CONCLUSIONS: There is considerable potential to reduce the risk of a further major ischaemic event in patients with established coronary disease. This can be achieved by effective lifestyle intervention, the rigorous management of blood pressure and cholesterol, and the appropriate use of prophylactic drugs.